A Natural Sum

Calculus Level 4

Find the sum of the series

n = 2 ln ( 1 1 n 2 ) \displaystyle \sum _{ n=2}^{\infty }{ \ln{\left( 1-\frac{1}{n^2} \right )} }

Round the answer to two decimal places.


The answer is -0.69.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Michael Mendrin
Aug 30, 2014

L o g ( ( 1 2 3 2 ) ( 2 3 4 3 ) ( 3 4 5 4 ) . . . ) = L o g ( 1 2 ) Log\left( \left( \frac { 1 }{ 2 } \frac { 3 }{ 2 } \right) \left( \frac { 2 }{ 3 } \frac { 4 }{ 3 } \right) \left( \frac { 3 }{ 4 } \frac { 5 }{ 4 } \right) ... \right) =Log\left( \frac { 1 }{ 2 } \right)

How did you get to that argument product?

John M. - 6 years, 9 months ago

Log in to reply

Well, sum of logs is the log of the products, isn't it? Then we have for each n the product term (n-1)(n+1)/(n)(n)

Michael Mendrin - 6 years, 9 months ago

Log in to reply

oh WHOA that's clever! Nice one

John M. - 6 years, 9 months ago
John M.
Aug 30, 2014

ln ( 1 1 n 2 ) = ln ( n 2 1 n 2 ) = ln ( n + 1 ) ( n 1 ) n 2 = ln [ ( n + 1 ) ( n 1 ) ] ln n 2 \ln{(1-\frac{1}{n^2})}=\ln{(\frac{n^2-1}{n^2})}=\ln{\frac{(n+1)(n-1)}{n^2}}=\ln{[(n+1)(n-1)]}-\ln{n^2}

= ln ( n + 1 ) + ln ( n 1 ) 2 ln n = ln ( n 1 ) ln n ln n + ln ( n + 1 ) =\ln{(n+1)}+\ln{(n-1)}-2\ln{n}=\ln{(n-1)}-\ln{n}-\ln{n}+\ln{(n+1)}

= ln n 1 n [ ln n ln ( n + 1 ) ] = ln n 1 n ln n n + 1 =\ln{\frac{n-1}{n}}-[\ln{n}-\ln{(n+1)}]=\ln{\frac{n-1}{n}}-\ln{\frac{n}{n+1}} .

Let s k = n = 2 k ln ( 1 1 n 2 ) = n = 2 k ( ln n 1 n ln n n + 1 ) s_k=\sum _{ n=2}^{k }{\ln{(1-\frac{1}{n^2})}}=\sum _{ n=2}^{k}{(\ln{\frac{n-1}{n}}}-\ln{\frac{n}{n+1}}) for k 2 k \ge 2 .

Then

s k = ( ln 1 2 ln 2 3 ) + ( ln 2 3 ln 3 4 ) + . . . + ( ln k 1 k ln k k + 1 ) = ln 1 2 ln k k + 1 , s_k=(\ln{\frac{1}{2}}-\ln{\frac{2}{3}})+(\ln{\frac{2}{3}}-\ln{\frac{3}{4}})+...+(\ln{\frac{k-1}{k}}-\ln{\frac{k}{k+1}})=\ln{\frac{1}{2}}-\ln{\frac{k}{k+1}}, so

n = 2 ln ( 1 1 n 2 ) = lim k ( ln 1 2 ln k k + 1 ) = ln 1 2 ln 1 = ln 1 ln 2 ln 1 = ln 2 . \sum _{ n=2}^{\infty}{\ln{(1-\frac{1}{n^2})}}=\lim_{k\rightarrow \infty}{(\ln{\frac{1}{2}}-\ln{\frac{k}{k+1}})}=\ln{\frac{1}{2}}-\ln{1}=\ln{1}-\ln{2}-\ln{1}=\boxed{-\ln{2}}.

n = 2 ln ( 1 1 n 2 ) = n = 2 ln ( ( n + 1 ) n ( n 1 ) n ) \displaystyle \sum_{n=2}^{\infty} \ln (1-\frac{1}{n^{2}})=\displaystyle \sum_{n=2}^{\infty} \ln (\frac{(n+1)}{n} \cdot \frac{(n-1)}{n}) = n = 2 ( ln ( n + 1 ) ln ( n ) ) + n = 2 ( ln ( n 1 ) ln ( n ) ) =\displaystyle \sum_{n=2}^{\infty} (\ln (n+1) - \ln (n)) + \displaystyle \sum_{n=2}^{\infty} (\ln (n-1) - \ln (n)) = lim n ( ln ( n + 1 ) l n ( 2 ) ) + lim n ( ln ( 1 ) ln ( n ) ) =\displaystyle \lim_{n\to\infty} (\ln (n+1) - ln (2)) + \lim_{n\to\infty} (\ln (1) - \ln (n)) = ln ( lim n n + 1 n ) ln ( 2 ) =\ln (\lim_{n\to\infty} \frac{n+1}{n}) - \ln (2) = ln ( 1 ) ln ( 2 ) = ln ( 2 ) =\ln(1) - \ln (2)=-\ln (2)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...